Предмет: Алгебра,
автор: 1LUTIK1
Помогите плиз -11x+3(x-3)=-8x-9
Ответы
Автор ответа:
2
Объяснение:
-11х+3(х-3)=-8х-9
-11х+3х-9=-8х-9
-11х+3х+8х=-9+9
0х=0
х любое число
Автор ответа:
1
-11x+3(x-3)=-8x+9;
-11x+3x-9=-8x+9;
-11x+3x+8x=9+9;
0x=18(равно зачеркнуть)
Ответ: нет решения
SLAndh:
там -9
Похожие вопросы
Предмет: Русский язык,
автор: valochka
Предмет: Русский язык,
автор: Мыслительёмаё
Предмет: Русский язык,
автор: uliagolovachova
Предмет: Биология,
автор: катя4796
Предмет: География,
автор: yanet85